Adaptasi Crime Prevention through Environment Design (CPTED): Studi Kasus Fenomena Desain Fasilitas Publik - Wizaka, Wiyantara (Bina Nusantara University, 2012)
Crime issues are quite familiar with the Indonesian folks, especially those living in big cities. Many things have been attempted by various parties to prevent and minimize crime. So far these efforts are more likely as arrest and punishment rather than prevention because prevention is much more difficult and more complex. Therefore it is sensible that crime prevention should be executed not only by law forces but also all elements of society who are able to contribute directly or indirectly to this regard. If indeed it is the responsibility of all elements of society, what can be done by us as designers or architects to this matter? In this paper is discussed the phenomenon of adaptation of the Crime Prevention through Environmental Design (CPTED) concept in public facilities in some areas and abroad.